Characteristics of rural hospital services for people with dementia: Findings from the Hospital Dementia Services Project. (16th August 2013) - Bail, Kasia; Hudson, Charles; Grealish, Laurie; Shannon, Kay; Ehsen, Saraah; Peut, Ann; Gibson, Diane; Draper, Brian; Karmel, Rosemary
Abstract Objective To obtain information about aged care services in rural New South Wales public hospitals, and to describe key operational aspects of their service delivery models. Design A mixed methods design was used to combine data collected from: (i) a survey of public hospitals and (ii) qualitative site visits in a sample of eleven rural sites. Setting Rural public hospitals in NSW, Australia. Participants Qualitative data were collected from multidisciplinary clinicians, managers and community service providers who participated in site visits in 2010 and from surveys of NSW public hospitals in 2009/10 about aged care and dementia services. Results Survey and site visit findings demonstrated that rural hospitals have fewer secure beds for managing patients with disturbed behaviour due to dementia and delirium and fewer speciality aged care staff than metropolitan hospitals. Site visit participants also described how secure environments can aid care for people with dementia even in the absence of clinical specialists. Conclusion The care of people with dementia in rural hospitals is constrained by access to specialist aged care staff and the physical environment of the hospital. Clinicians are adept at maximising resources to manage diagnosis and transitions for people with dementia. Further understanding of how key operational aspects of clinical leadership and environmental modifications impact on a range of patient outcomes would be valuable.